Restorative Justice as a Form of Indonesian Pluralism in Realizing the Development of Criminal Law in the Era of Globalization - Fitria Ramadhani Siregar (International Journal of Society and Law, 2024)
Children are Allah's entrustment to parents, society, nation and country heirs of Islamic teachings (revelation of Allah Almighty) which will later prosper the world as rahmatan lil 'âlamîn. That every child has the right to protection from violence or persecution and discrimination as mandated in the 1945 Constitution of the Republic of Indonesia. The rights of children as victims of criminal acts of maltreatment include, such as treatment, psychological rehabilitation and compensation. This research was conducted with normative legal research. Normative legal research is research that places law as a building system of norms, consisting of principles, norms, rules of laws and regulations, court decisions, agreements and doctrines.